The Effect of Empowering Leadership on Creative Performance: An Analytical Research in Diyala General Company - Mohammed Abdullah, Worood; Kadhim Saeed, Hadeel (Journal of Economics and Administrative Sciences, 2024)
This research aims to explore the impact of multifaceted empowering leadership (power and responsibility delegation, autonomous decision-making, knowledge sharing, skill development, and innovative performance training) as an independent variable in achieving multi-dimensional creative performance (authenticity, fluency, flexibility, self-efficacy) as a dependent variable. The research also aims to enhance the quality of empowering leadership among a sample of 117 leaders in Diyala Public Company through effective modern leadership styles. The research specifically focuses on the importance of creative performance in this sample. Data was collected using a questionnaire as the main tool and statistical methods such as standard deviation, Sobel test, Pearson correlation coefficient, and software such as SPSS and Excel. The results showed a significant positive and direct relationship between empowering leadership and creative performance in general. The research concluded that empowering managers in Diyala Public Company with the authority to make necessary changes is an important step to improve overall work processes. This empowering helped managers effectively adapt to challenges and increase efficiency in responding to changing market demands. By empowering managers to improve processes, the company succeeded in promoting innovation and increasing productivity, ultimately enhancing its position in the market and achieving sustainable and clear success. Research type: Research paper